2018
DOI: 10.1126/sciadv.aas9365
|View full text |Cite
|
Sign up to set email alerts
|

Powering the ABC multidrug exporter LmrA: How nucleotides embrace the ion-motive force

Abstract: Researchers study how different forms of metabolic energy are coupled to drug extrusion by an ATP-binding cassette transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Our findings for MsbA and MsbA-MD are reminiscent of previous studies on LmrA-MD which demonstrated apparent ethidium-proton symport [57]. Most recently, we have extended these studies to full-length LmrA in cells and proteoliposomes, and used electrophysiological studies on LmrA in planar lipid bilayers and giant unilamellar liposomes to characterise the stoichiometry of the ion transport reaction in detail [58]. The efflux of one ethidium + and one H + by LmrA occurs in symport with one Cl -, in counter-transport to two Na + , in an electrogenic reaction that is driven by the inwardlydirected sodium motive force in cells (interior negative and low).…”
Section: Ion Transport Reactionssupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings for MsbA and MsbA-MD are reminiscent of previous studies on LmrA-MD which demonstrated apparent ethidium-proton symport [57]. Most recently, we have extended these studies to full-length LmrA in cells and proteoliposomes, and used electrophysiological studies on LmrA in planar lipid bilayers and giant unilamellar liposomes to characterise the stoichiometry of the ion transport reaction in detail [58]. The efflux of one ethidium + and one H + by LmrA occurs in symport with one Cl -, in counter-transport to two Na + , in an electrogenic reaction that is driven by the inwardlydirected sodium motive force in cells (interior negative and low).…”
Section: Ion Transport Reactionssupporting
confidence: 78%
“…Although mutations in NBDs of LmrA and MsbA that inactivate ATP hydrolysis (e.g. deletion of lysine residue in Walker A in MsbA-ΔK382 and LmrA-ΔK388) inactivate ethidium transport in metabolically-active cells [53,56,58], both deletion mutants reconstituted in proteoliposomes are transport-active in the presence of appropriate electrochemical ion gradients. This suggests that, when nucleotide is present, nucleotide hydrolysis is compulsory for transport activity to prevent nucleotide trapping of LmrA.…”
Section: Ion Transport Reactionsmentioning
confidence: 99%
“…For example, Hoechst was used in studies of drug efflux-based antibiotic resistance in Salmonella enterica serovar Typhimurium 8,9 and Acinetobacter baumannii 10,11 , and in transport measurements for the ABC multidrug transporters LmrA from Lactococcus. lactis [12][13][14] , Sav1866 from Staphylococcus aureus 15 , MsbA and YbhFSR from E. coli 16,17 , and PatAB from Streptococcus pneumoniae 18 . Hoechst transport assays were used in studies of secondary-active multidrug and toxic compound extrusion (MATE) transporters VcmA from Vibrio cholerae 19 and AbeM from A. baumannii 20 , and in studies of a novel natural product inhibitor of the major facilitator superfamily (MFS) multidrug transporter NorA from Staphylococcus aureus 21 .…”
mentioning
confidence: 99%
“…13 μl for band 1 and 15 μl for bands 2-5 was loaded on QExactive for 1h runs. All LC-MS/MS experiments were performed using a Dionex Ultimate 3000 RSLC nanoUPLC (Thermo Fisher Scientific Inc, Waltham, MA, USA) system and a QExactive Orbitrap mass spectrometer (Thermo Fisher Scientific Inc, Waltham, MA, USA) as described recently [20]. The mass spectrometry proteomics…”
Section: In Gel Digestion and Mass Spectrometrymentioning
confidence: 99%